Association of Vitamin D with Obesity in Premenstrual Syndrome: A Study of Female Population of Hyderabad, Sindh - Aqsa Naeem, Urooj Bhatti, Sarwat Batool, Khalida Shaikh, Arsalan Uqaili, Keenjher Rani (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction/Objectives: The affiliation between decreased vitamin D and obesity is well built up. Females with Premenstrual Syndrome (PMS) are more prone to gain weight. Obese women’s low calcifediol levels are impacted by diets and inactive lifestyles. The study focused to discover out the relationship between vitamin D and obesity in premenstrual syndrome females. Study design: Cross-sectional study Place and Duration: OPD-Gynecology, Liaquat University of Medical &Health Sciences (LUMHS), Jamshoro and Hyderabad in collaboration with Physiology Department LUMHS Jamshoro and Diagnostic and Research lab Hyderabad. Materials & Methods: Two hundred fifty (250) females between15-45 years with a history of PMS were selected for this study. Information was collected on marital status, vitamin D3 levels, PMS intensity, and BMI. The Chi-square test compared the vitamin D levels with BMI and PMS scores. Results: Mean age of the patients was 29.89±5.206 years. 64.8% of patients were married. 42.8% had normal weight and 40.8%were obese. 35.2% of patients had mild PMS scores and 36.4% had extreme PMS. 61.2% of patients had vitamin D lack with only 4.8% having adequate serum vitamin D levels. 22.8% of normal-weight patients had inadequate serum vitamin D levels. 35.6% of obese patients had vitamin insufficiency in their blood. The relationship between obesity and vitamin D levels was significant (P-value: 0.001). 18.8% of patients who had mild PMS scores had deficient serum vitamin D levels. The relationship between PMS scores and vitamin D levels was remarkable (P-value: 0.001). Practical implication The advantages of 25(OH) D supplementation/repletion on bone health are well known. Although there is a biological plausibility linking the status of vitamin D and obesity supported by basic and clinical research findings, basic research is necessary to know the molecular pathways involved in this association. Also this study will help the community to decrease the PMS symptoms by taking vitamin D supplements. Those females who take the vit D prior their PMS stage will be prevented from severe symptoms. Conclusion: We found a significant, inverse relationship between vitamin D levels and BMI, showing that losing weight through vitamin D and calcium-enriched diets may result in typical vitamin D levels, and so PMS may be treated. Keywords: Vitamin D (Vit D), Premenstrual Syndrome, body-mass index (BMI), obesity, women